The Surveillance in Health Basic: perspectives to reach the Surveillance in Health - Faria, Liliam Saldanha; Bertolozzi, Maria Rita (Revista da Escola de Enfermagem da USP, 2010)
The Surveillance in Health is constituted as an Assistance Model with potential to reorganize the working processes. This study was developed to identify and analyze surveillance practices in the Primary Health Care field, in a region of São Paulo City-Brazil. Interviews were performed with 14 individual, from February to April 2006: health workers and administrators who had been operating in the Epidemiologic Surveillance area of health basic units. The speeches were analyzed based on the social theory of the health-disease process and by the materialistic interpretation of the labor process. It was verified that their work was fragmented. The precariousness of the working structure, the lack of professional qualification and of management-political support, besides the lack of participation from the population were all identified as barriers that limit health surveillance practices. It was concluded that, in a local level, there is a potential to change the organization of the working process in health and meet the health needs of the population through a Health Surveillance Model.